DIFFUSION WEIGHTED IMAGE (DWI) AND MAGNETIC RESONANCE SPECTROSCOPY (MRS) OF MASS LIKE LESIONS IN THE BRAIN AS CORRELATED TO HISTOPATHOLOGY. - METARUGCHEEP, Pichest; PHUDHICHAROENRAT, Suchart; KIATHIRANNON, Nitat; CHANYAWATTIWONGES, Somsak (The ASEAN Journal of Radiology, 2023)
Bachground and purpose: DWI and MRS have been used for the differentiation and grading of the brain tumors for more than 10 yrs. We attempted to study the diagnostic efficacy of these two techniques in MR imaging as correlated to the histopathology.